An Exploratory Study on The Relationship of Religious Metacognition with Depression and Suicidal thoughts - Mohammad Hosien Salarifar; Mansour Salehi; Zinab Syarfard (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2020)
Abstract Major depressive disorder is one of the most common mental disorders. Depression is associated with hopelessness, helplessness and organized cognitive errors in thought. Suicide is a major public health problem and Suicide rates are rising among societies. For this reason, finding the predictor and effective factors in depression is so important. This survey is to assess the relationship of religious metacognition with depression and suicidal thoughts. The research method of this study is a correlation. The study population consisted of students of The University of Birjand in the year 1398. The participants were selected via a random cluster sampling method (n=205). Participants completed the questionaries’ of religious metacognition (Salarifar, 1398), depression (Beck et al, 1966) and suicidal thoughts (Beck, 1979). The data were analyzed with the Pearson correlation coefficient and stepwise multiple regression. The results showed, there was a significant negative correlation between depression and suicidal thoughts with religious metacognition, but depression has a positive and significant relationship with suicidal thoughts. The result of regression indicated that components of religious metacognition explained 28% of the variance of depression and 25% of the variance of the suicidal thoughts. It was found that may religious metacognition components can serve as an inhibitory mechanism with depression and suicidal thoughts. According to the results of this study, it may be concluded that with the boosting religious metacognition, the rate of depression and suicidal thought would be decreased.